2021
DOI: 10.18332/tid/136418
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smoking on oral health and patient assessment of tobacco cessation support from Turkish dentists

Abstract: INTRODUCTION Dentists are in a critical position to help patients quit smoking. This study analyses the effectiveness of Turkish dentists in smoking cessation as part of routine patient care. METHODS An in-person cross-sectional survey on previous dental visit experiences was completed by 226 patients recruited from the Department of Periodontology, Eskisehir Osmangazi University, Turkey, from March 2019 to September 2019. The questionnaire included topics on patient’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Subsequently, seven full-texts were screened which did not require contacting the authors. Based on eligibility criteria, seven studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] were finally included in the present systematic review, as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, seven full-texts were screened which did not require contacting the authors. Based on eligibility criteria, seven studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] were finally included in the present systematic review, as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Costa et al [ 60 ] and Beklen et al [ 64 ] reported lower periodontal probing depth values and a lower percentage of sites with a PD ≥ 5 mm in ex-smokers and non-smokers compared to current smokers. No differences in PD values were in anyway observed by Karaaslan et al and Liu et al [ 58 , 63 ] in relation to a smoking habit or smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous work of our group, we found that individuals know the importance of oral health and the necessity of hygiene. On the other hand, even though the patients know that smoking would damage their oral health, they continue to smoke 26 . Now we have a much clearer picture of smokers, in which irregular brushing is more common for ex-smokers and social smokers.…”
Section: Discussionmentioning
confidence: 99%